Geçici konkordato mühleti ve sonuçları - Çınar, Süleyman Serhan (My University, 2019)
Marmara Üniversitesi Sosyal Bilimler Enstitüsünde olarak hazırlanan bu çalışmada güncel kararlar ışığında İcra ve İflas Kanunu (İİK) madde 285 – 309 arasında düzenlenen adi konkordatoda geçici mühlet yargılaması incelenmiştir. Tezimizin birinci bölümünde genel olarak konkordato kurumu incelenmiş, ikinci bölümde adi konkordatoda geçici mühletin amacı ve hukuki niteliği üzerinde durulmuş, üçüncü bölümde geçici mühlet yargılaması ve geçici mühletin sonuçları incelenmiş, son olarak dördüncü bölümde ise geçici mühletin sona ermesi konusu ele alınmıştır.

In this study, which has been prepared as a master thesis at Marmara University Social Sciences Institute, proceeding of provisionary period in concordat, which is regulated in article 285 – 309 of Execution and Bankruptcy Law, has been examined in the light of recent court decisions. The first part of thesis analyses concordat regulation, the second part focuses on the aim of provisionary period in concordat and legal nature of provisionary period and third part explains proceeding of provisionary period and consequences of provisionary period. Finally, the fourth part of the thesis handles termination of provisionary period.
Keywords: Civil law; Konkordato Concordat; Medeni hukuk